Book Review ~ Distance Education and Distributed Learning. Editors: Editors: Charalambos Vrasidas and Gene V. Glass - Ramesh C. Sharma (International Review of Research in Open and Distributed Learning, 2004)
As universities and educational institutions around the globe strive to adopt and expand the use of information technologies in their teaching/ learning offerings, this book, Distance Education and Distributed Learning, will help those engaged in coming to grips with this fundamental paradigm shift taking place in education. This book addresses a wide range of issues related to distance education and online technologies. In the broadest sense, today’s technology-driven changes in distance education will help make students and teachers more aware of social justice and equity through the use of technology used to solve real life problems irrespective of time and space, culture and ability to participate. Distance education has changed over the years, and even more so since the introduction of Web-based technologies. Today, the trend is towards globalization and collaboration among educational institutions. Distance educators and students now have access to emerging opportunities to engage in higher quality education irrespective of time and space.